VP16 fusion induces the multiple‐knockout phenotype of redundant transcriptional repressors partly by Med25‐independent mechanisms in Arabidopsis. Issue 20 (19th August 2014) - Fujiwara, Sumire; Sakamoto, Shingo; Kigoshi, Keiko; Suzuki, Kaoru; Ohme-Takagi, Masaru
Abstract : Biological functions of only some plant transcriptional repressors are known owing to the lack of knockout lines or unclear phenotypes because of redundancy. Here we show that strong viral activation domain VP16 fusion to the transcriptional repressor FLOWERING LOCUS C reversed its function and caused a stronger phenotype than that of the multiple‐knockout line of redundant genes, suggesting the potential of this technique to identify transcription factor function that cannot be detected in a single‐knockout line. Loss‐of‐function of transcriptional coactivator Mediator25 did not affect VP16 activity despite their in vivo interaction, suggesting the existence of other key mechanism(s) in plants. Abstract : VP16 fusion dominantly reverses Arabidopsis transcriptional repressor function. VP16 fusion causes a stronger phenotype than that of double loss‐of‐function of redundant genes. These data show the efficacy of VP16 fusion for repressor studies in plants. Arabidopsis Med25 interacts with VP16 in vivo. med25 loss‐of‐function does not affect activation by VP16.